The Public–Private Partnership for the Enhancement of Unused Public Buildings: An Experimental Model of Economic Feasibility Project - Calabrò, Francesco; Della Spina, Lucia (Sustainability, 2019)
This article is part of the debate on the economic evaluation of urban regeneration projects to be implemented through partnership forms between public and private subjects. It illustrates the results of the research activity carried out by the authors, aimed at developing innovative tools to verify the economic feasibility and the sustainability of projects for the reuse of unused public buildings. Particularly, the study made it possible to develop an experimental model of economic feasibility project to be used in the. The model aims at verifying if the economic conditions are satisfied, and which ones, if any, are appealing for the private involvement within the realization and/or management of collective utility interventions. Significant points of the model are: (1) The inclusion of real estate re-use projects in the wider context of urban and territorial regeneration; (2) the adoption of criteria to assess costs and revenues remarkably eligible, in the authors’ opinion, to understand the effective economic feasibility and/or sustainability of reuse projects, even under the framework of reliable techniques as the ‘Cash Flow Analysis’ and the ‘Discounted Cash Flow Analysis’.